Pengaruh Perubahan Digitalisasi dalam Organisasi Himalika Universitas Semarang - Melani Melani; Fitrotul Afifah; Annisa Putri Sofyan (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This study analyzes the influence of digitalization changes in the Himalika Organization by focusing on organizational structure, work procedures, and the use of information technology. The background of this research is the need for organizations to adapt to the development of information technology in the era of globalization. The purpose of this study is to understand the level of acceptance and adaptability of organizational members to digitalization changes, as well as to identify the factors that affect the success of these changes. The method used was a quantitative approach by collecting data through a questionnaire filled out by 67 respondents who were members of the Himalika Organization. The results of this study state that regular changes, improvements, and innovations are important for Himalika in improving operational efficiency, adapting to environmental changes, and creating new solutions. By accepting and responding to change well, willing to accept, Himalika can succeed in this ever-evolving environment.